Frontispiece: Excess Electron Transfer through DNA Duplexes Comprising a Metal‐Mediated Base Pair. Issue 43 (1st August 2017) - Hensel, Susanne; Eckey, Kevin; Scharf, Philipp; Megger, Nicole; Karst, Uwe; Müller, Jens
Abstract : DNA‐mediated charge transfer represents a topical area of research. The influence of the site‐specific introduction of a metal ion into the base pair stack is a matter of current debate. In their communication onpage 10244 ff., U. Karst, J. Müller et al. contribute to this debate by reporting an experimental study on excess electron transfer across a metal‐mediated base pair within a DNA double helix. To this end, LC/ICP‐MS was applied for the first time to quantify the electron‐transfer efficiency. The data suggest that a thymine–Hg II –thymine base pair influences charge transfer in the same way as a thymine:thymine mispair does.